Monetary and Fiscal Remedies for Deflation - Auerbach, Alan J; Obstfeld, Maurice (American Economic Review, 2004)
Prevalent thinking about liquidity traps suggests that the perfect substitutability of money and bonds at a zero short-term nominal interest rate renders open-market operations ineffective for achieving macroeconomic stabilization goals. In an earlier paper, we showed that this reasoning does not hold, that open-market operations can provide substantial macroeconomic benefits and facilitate the use of powerful fiscal policy tools even in a liquidity trap. In this paper, we consider an alternative approach that has been suggested for use in a liquidity trap, a scheduled increase in consumption tax rates. We find that such a policy could, indeed, increase short-run consumption, but would be less effective at increasing welfare or accelerating a country's exit from a liquidity trap. Though a variant of this tax policy might induce exit from a liquidity trap, the impact of welfare is negative in this case as well. We also argue that this alternative tax-rate-based approach is subject to more severe credibility problems than the monetary policy approach explored in our original paper.